Logistic Ecosystems and Platforms on Sharing Economy - Fakher, Mehrdad (Management Strategies and Engineering Sciences, 2026)
This study examines logistics ecosystems and platforms in the sharing economy and seeks to achieve multiple goals that can help improve the performance and efficiency of these systems. The first goal is to design and implement operational and software solutions that lead to increased supply chain efficiency by improving coordination between stakeholders and effective resource management. Second, the establishment of service quality standards in logistics platforms and the examination of methods and tools for evaluating and improving performance have been considered in order to ensure service quality and increase user satisfaction. Third, promoting a culture of cooperation and trust between users and service providers, through training and information, is considered as one of the key factors for the success of sharing platforms. Fourth, the establishment of decision-making and data analysis centers is essential for the optimal use of collected information in order to improve management strategies and decisions. Ultimately, developing and proposing environmental and economic sustainability strategies that help improve performance and reduce negative impacts in the long term is a strategic goal. This thesis addresses the performance and efficiency of logistics platforms in the sharing economy by providing innovative and practical solutions and offers solutions to existing challenges.